Aortic Waveform Analysis to Individualize Treatment in Heart Failure. (February 2017) - Wohlfahrt, Peter; Melenovsky, Vojtech; Redfield, Margaret M.; Olson, Thomas P.; Lin, Grace; Abdelmoneim, Sahar S.; Hametner, Bernhard; Wassertheurer, Siegfried; Borlaug, Barry A.
Abstract : Background—: Afterload reduction is a cornerstone in the management of patients with heart failure (HF) and reduced ejection fraction. However, arterial load and the effect of HF therapies on afterload might vary between individuals. Tailoring vasoactive medicines to patients with HF based upon better understanding of arterial afterload may enable better individualization of therapy. Methods and Results—: Subjects with HF and reduced ejection fraction underwent aggressive titration of vasoactive HF therapies with assessment of central aortic waveforms analyzed using pulse wave, wave separation, and arterial reservoir models. Clinical response to treatment was assessed using the 6-minute walk test distance, which increased in 25 subjects and decreased or remained unchanged in 13. Subjects with improvement on therapy displayed higher aortic pressure wave pulsatility (central pulse pressure [PP], reflected pressure wave, and reservoir pressure) at study entry compared with subjects without improvement (all P <0.05). Parameters derived by the arterial analysis methods were strongly correlated with one another and displayed similar ability to predict improvement. Aortic pressure pulsatility significantly decreased in subjects with functional improvement, whereas no change was observed in patients without functional improvement ( P for interaction <0.05). These differences in arterial load at baseline and on therapy were not apparent from conventional brachial artery cuff pressure assessments. Conclusions—: Increased aortic pressure wave pulsatility and greater decrease in pulsatility on treatment are associated with functional improvement in patients with HF and reduced ejection fraction receiving aggressive vasodilator titration. These differences are not identifiable using brachial cuff pressures. Central aortic waveform analysis may enable better individualization of vasoactive therapies in chronic HF and reduced ejection fraction. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00588692. Abstract : Supplemental Digital Content is available in the text.